Self-Regulated Learning in Elementary School Students: Trends, Strategies, and Impact on Learning Outcomes - Mufarrahatus Syarifah; Putu Eka Suarmika; Nuris Hidayat; Muslihati Muslihati; Siti Faizah (Journal of General Education and Humanities, 2026)
Self-regulated learning (SRL) has become an essential competency for elementary school students in the twenty-first century, particularly in supporting independent learning, academic achievement, and learning adaptability. This study aimed to systematically review research trends, instructional strategies, and the impact of SRL on learning outcomes among elementary school students. The study employed a Systematic Literature Review (SLR) approach using the PRISMA framework. Articles were collected from Scopus-indexed published between 2016 and 2026. Bibliometric mapping was conducted using VOSviewer to analyze research trends. The search process identified 194 articles for trend analysis. Meanwhile, studies discussing instructional strategies and learning outcomes were selected using specific inclusion criteria emphasizing quantitative and experimental research designs. The findings revealed that SRL research in elementary education has developed into a multidimensional field closely associated with self-efficacy, motivation, feedback, online learning, goal setting, and academic achievement. The most commonly implemented strategies for developing SRL included metacognitive instruction, goal-setting activities, reflective learning, collaborative learning, self-assessment, gamification, and technology-assisted learning environments. In addition, the reviewed studies consistently demonstrated that SRL positively contributes to students’ academic achievement, learning motivation, problem-solving skills, and independent learning behaviors. Overall, this review highlights the importance of strengthening SRL through explicit instructional support and technology-enhanced learning environments to foster adaptive and independent learners in elementary education.